Love-Based Curriculum as the Foundation for Humanizing Education in the Digital Era - Suprih Hartanto (Civiliza Publishing, Indonesia., 2025)
Learning environments are increasingly mediated by artificial intelligence, online platforms, big data, and automated systems that promise efficiency, accessibility, and innovation. This study aims to examine the role of a love-based curriculum as a foundational approach for humanizing education in the digital era. Employing a qualitative literature review method, this research analyzes relevant academic journals, scholarly books, and authoritative publications that discuss love-centered pedagogy, humanistic education, curriculum development, and digital learning. The collected data were systematically examined through thematic content analysis to identify key concepts, theoretical perspectives, and patterns related to the integration of love-based values in educational practice. The findings indicate that a love-based curriculum significantly contributes to humanizing education by fostering caring teacher–student relationships, promoting holistic learner development, and guiding the ethical and meaningful use of digital technology. Furthermore, the study reveals that embedding love as a core curriculum value enhances learners’ emotional well-being, moral character, and social responsibility, thereby ensuring that educational innovation in the digital era remains aligned with human dignity and humane educational goals.